Can insect body pollen counts be used to estimate pollen deposition on pak choi stigmas - Howlett, B.G.; Walker, M.K.; Rader, R.; Butler, R.C.; Newstrom-Lloyd, L.E.; Teulon, D.A.J. (New Zealand Plant Protection, 2011)
Measuring pollen deposition onto stigmas by insects is one technique used to assess pollinator effectiveness but it can be unpredictable and timeconsuming as insects must visit test flowers This study examined whether a measurement of pollen grains from flowervisiting insects could be used to predict pollen deposited on stigmas Individuals were collected from four bee and six fly species as they visited pak choi flowers in commercial and trial seed fields to assess their body pollen Pollen was removed from insects by pressing their bodies (excluding activelycollected pollen on bees hind legs) with a cube of gelatinefuchsin In this study there appears to be a strong correlation between mean estimated pollen counts for each insect species and previously published data recording mean number of pollen grains deposited on stigmas for the same species Therefore the measurement of pollen grains directly from flowervisiting insects shows potential as a quicker and easier technique to assess pollinator effectiveness as insects can be directly collected from flowers